2018
DOI: 10.1016/j.biosystemseng.2018.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Automatic cough detection for bovine respiratory disease in a calf house

Abstract: In calf rearing, bovine respiratory disease (BRD) is a major animal health challenge. Farmers incur severe economic losses due to BRD. Additional to economic costs, outbreaks of BRD impair the welfare of the animal and extra expertise and labour are needed to treat and care for the infected animals. Coughing is recognised as a clinical manifestation of BRD. Therefore, the monitoring of coughing in a calf house has the potential to detect cases of respiratory infection before they become too severe, and thus to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 29 publications
(40 reference statements)
2
46
0
Order By: Relevance
“…In addition, manual labelling was used to score the quality of measured data corresponding to 3 ratings [34]. Overlapped sounds labelled as rating 1 were not selected as training and testing datasets due to their complex acoustic features and limitations in sound source separation technology.…”
Section: Sound Signal Pre-processing and Labellingmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, manual labelling was used to score the quality of measured data corresponding to 3 ratings [34]. Overlapped sounds labelled as rating 1 were not selected as training and testing datasets due to their complex acoustic features and limitations in sound source separation technology.…”
Section: Sound Signal Pre-processing and Labellingmentioning
confidence: 99%
“…The objective was to detect the calls of hens. A good selection of each sound event such as the exact beginning and end, will improve the success rate of the classification algorithm [34]. Filtered hen calls contain more energy than the background noise, so the envelope of energy method was selected to perform the sound detection.…”
Section: Automatic Sound Event Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies have been reported to detect abnormalities in livestock using sound sensors to guarantee animals' health and welfare without affecting farm budgets. These methods are not only cost effective, as they are cheaper than other sensors, but also more practical and animal friendly because they collect data constantly for 24 h a day without causing any stress or discomfort to the animals [2][3][4][5][6][7][8]. In the case of chickens, certain studies that employed sound data include a study of hens' stress caused by temperature changes based on the results of vocalization analysis [2]; studies on the detection of respiratory diseases based on broilers' sneezing and coughing [3,4]; and a study that attempted to detect avian influenza using chicken sound data [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of chickens, certain studies that employed sound data include a study of hens' stress caused by temperature changes based on the results of vocalization analysis [2]; studies on the detection of respiratory diseases based on broilers' sneezing and coughing [3,4]; and a study that attempted to detect avian influenza using chicken sound data [5]. Similarly, in the case of cattle, certain studies employed sound to detect cows' estrous [6] and respiratory diseases [7,8]. In conclusion, sound data are important as they allow retrieving information that can be useful for detecting abnormalities in livestock.…”
Section: Introductionmentioning
confidence: 99%